Outstanding effect of the conformational restriction of isoquinolines: Hints for the development of optimized antimicrobial agents - Özçelik, Berrin; Sheikh, Javed I.; Orhan, I. E.; Juneja, Harjeet D.; Bennani, Brahim; Kerbal, Abdelali; Cavalcanti, Suellen Melo Tibúrcio (My University, 2013)
Conformational restriction constitutes a useful strategy of molecular modification for the design of new potential drug candidates. Herein we present the planning, antimicrobial evaluation, and establishment of structure-activity relationship (SAR) data for some isoxazole (3a-k, 8a-c, and 9a-c) and pyrazole (5a-h) derivatives. These derivatives were structurally designed by conformational restriction followed by bioisosteric exchange of previously described antimicrobial isoquinolines (1a-c). Some of these more conformationally restricted derivatives present improved properties as new antibacterial drug candidates. © 2012 Springer Science+Business Media B.V.
Keywords: 1,2-Isoxazole; 1,2-Pyrazole; Antibacterial agents; Isoquinolines; Restriction conformation